2018
DOI: 10.1519/jsc.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Tapering Practices of Strongman Athletes

Abstract: Winwood, PW, Dudson, MK, Wilson, D, Mclaren-Harrison, JKH, Redjkins, V, Pritchard, HJ, and Keogh, JWL. Tapering practices of strongman athletes. J Strength Cond Res 32(5): 1181-1196, 2018-This study provides the first empirical evidence of how strongman athletes taper for strongman competitions. Strongman athletes (n = 454) (mean ± SD: 33.2 ± 8.0 years, 178.1 ± 10.6 cm, 108.6 ± 27.9 kg, 12.6 ± 8.9 years general resistance training, 5.3 ± 5.0 years strongman implement training) completed a self-reported 4-page … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(89 citation statements)
references
References 35 publications
17
71
1
Order By: Relevance
“…Researchers have also demonstrated that large reductions in training load may be beneficial after overload training in Taekwondo (50%) 9 , Rugby League (≈55%) 10, and Judo (≈55%) 8 athletes. Thus, the reduction in training volume reported by CrossFit athletes in the current study meets the recommendations of 41-60% volume reduction found to be most effective by Bosquet et al 21 Elite CrossFit athletes were found to begin tapering later than Powerlifters, and perform their final training session closer to competition than other strength athlete 13,19,20 . Pritchard et al 19 found that elite New Zealand Powerlifters began tapering 16.8 ±6.3 days out from an event, similarly Grgic et al 20 found that Croatian Powerlifters began tapering 18 ±8 days out.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Researchers have also demonstrated that large reductions in training load may be beneficial after overload training in Taekwondo (50%) 9 , Rugby League (≈55%) 10, and Judo (≈55%) 8 athletes. Thus, the reduction in training volume reported by CrossFit athletes in the current study meets the recommendations of 41-60% volume reduction found to be most effective by Bosquet et al 21 Elite CrossFit athletes were found to begin tapering later than Powerlifters, and perform their final training session closer to competition than other strength athlete 13,19,20 . Pritchard et al 19 found that elite New Zealand Powerlifters began tapering 16.8 ±6.3 days out from an event, similarly Grgic et al 20 found that Croatian Powerlifters began tapering 18 ±8 days out.…”
Section: Resultssupporting
confidence: 83%
“…A comprehensive CrossFit tapering practices survey was distributed directly to eligible athletes online, this survey aimed to determine how elite CrossFit athletes taper for their major CrossFit competitions. The survey was adapted from an online survey previously used with Strongman athletes 13 , which was shown to produce reliable responses 14 . The message sent to athletes briefly described the research objectives and invited them to participate via a link to the survey.…”
Section: Experimental Overviewmentioning
confidence: 99%
“…The full text of the 45 articles was further assessed for eligibility and 29 articles were excluded due to lacking details regarding methodology (n = 17), not providing specifics about a taper or training cessation being used (n = 9), or not being aimed at achieving maximal strength for powerlifting performance (n = 3). There were two surveys involving powerlifters [35,36] and one survey involving strongman competitors [37] that were included in the review that did not provide performance outcomes. However, inclusion of these studies can be justified considering they provide the most detailed account of tapering to date for powerlifting performance.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…However, inclusion of these studies can be justified considering they provide the most detailed account of tapering to date for powerlifting performance. Excluding the large strongman tapering practices survey [37], studies involved sample sizes ranging from 5 to 44 subjects (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…With the increasing popularity of strongman as both a competitive sport and as a source of alternative strength and conditioning training exercises for athletes of wide sporting backgrounds, the quantity and quality of research on the sport of strongman is continuing to increase. This research has examined the training and tapering practices of strongman athletes (McManus, O'Driscoll, Coleman, & Wiles, 2016a;McManus, Wiles, Coleman, & O'Driscoll, 2016b;Waller, Piper, & Townsend, 2003;Winwood et al, 2018;Winwood, Keogh, & Harris, 2011;Zemke & Wright, 2011), how strength and conditioning coaches utilise strongman implements in their athletes' programmes (Winwood, Cronin, Keogh, Dudson, & Gill, 2014b), the physiological responses to strongman training (Berning, Adams, Climstein, & Stamford, 2007;Gaviglio, Osborne, Kelly, Kilduff, & Cook, 2015;Ghigiarelli, Sell, Raddock, & Taveras, 2013;Harris, et al, 2016;Winwood et al, 2015c;Woulfe, Harris, Keogh, & Wood, 2014) and the injury epidemiology of strongman athletes (Winwood, Hume, Cronin, & Keogh, 2014c). It should be acknowledged that some of this literature includes narrative reviews and/or opinion pieces on how strongman exercises could be best integrated into strength and conditioning programmes for non-strongman athletes.…”
Section: Introductionmentioning
confidence: 99%